EXTREME LASER RADIATION: PHYSICS AND FUNDAMENTAL APPLICATIONS : Third harmonic generation in the short-wavelength UV range by a single plasmonic nanostructure. (1st June 2016) - Melentiev, P N; Kuzin, A A; Afanasiev, A E; Balykin, V I
Abstract: The nonlinear optical interaction of laser radiation with nanostructures formed in gold and aluminium nanofilms has been experimentally studied. It is shown that, despite the high susceptibility χ3 of aluminium in comparison with gold, the third-harmonic generation efficiency at a wavelength of 260 nm is much higher for the nanostructures formed in a gold nanofilm because of the efficient excitation of a localised plasmon resonance at the fundamental frequency.